INTERACTION OF LOGISTICAL PROCESSES OF HOUSEHOLD AND THE ORGANIZATIONS OF TRADE - A.V. Zyrjanov; O.N. Zueva (Экономика региона, 2008)
Article is devoted to a problem of use of the logistical approach to research ïîòîêîâûõ processes of household and the organizations of trade on a commodity market and services. Households are considered as the collective subject of behaviour and a closing link of a logistical circuit. In work segmentation of the enterprises of retail trade for the proved choice of strategy of their development, formation target perspective programs is lead at a regional level in view of regional specificity. Affirms, that development, accommodation, quantitative and qualitative transformation of the organizations of trade and sphere of services directly depend on a standard of living of the population, solvent demand concrete Household.